IMPLEMENTASI STRATEGI PENANGANAN KRISIS KOMUNIKASI ERA DIGITAL: STUDI KASUS KONTEN YOUTUBE PODCAST DEDDY CORBUZIER BERSAMA RAGIL MAHARDIKA - Ramadhan Nanda Ivan; Oktaviane Annisa; Muhammad Aidil Armi (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
This paper discusses a case of a communication crisis experienced by a youtuber, where the manager of this crisis sparked a lot of criticism from his market share because of the lack of precise content. If juxtaposed with the norms and ethics where the channel's viewers are broadcasting, Indonesia. This study uses a qualitative approach approach where qualitative research as a scientific method is often used and carried out by a group of researchers in the social field. The method of collecting data is through observation, documentation, and literature review. The results of this study indicate that the topics presented in Deddy Corbuzier's podcast contain sensitive issues, namely LGBT. Unfortunately in Indonesia this issue is taboo and has a negative image. His podcast became controversial because he had a large amount of mass, at the time of the study his subscriber count touched 18.6 Million. Deddy Corbuzier managed to overcome the crisis that occurred by inviting religious leaders to correct the podcast he was doing. Deddy admitted his mistake because of the lack of forgiveness to the public for the misperceptions that occurred. In order to get rid of the public commotion, Deddy deleted the content with the yeast and was careful when talking about the issue.